Road Damage Analysis On Inter-City Roads Using Pavement Condition Index (PCI) Approach In West Java Indonesia - Mira Lestira Hariani; Ahmad Taufik; Suparman Suparman; Agus Kosasih; Ohan Farhan (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Poor road infrastructure conditions have a significant impact on transportation efficiency, user safety, and logistics costs, especially in areas with tropical climates and heavy vehicle traffic such as in West Java. This study aims to evaluate the condition of road pavement on the Jangga–Cikamurang Road section in Indramayu Regency using the Pavement Condition Index (PCI) method. The survey was conducted visually along 1 kilometer of road, which was divided into 10 segments of 100 meters each. Observations included identification of the type of damage, severity, and extent of damage in each segment. The results of the study showed that the most dominant types of damage were alligator cracking (42.47%) and depression (33.63%) with high severity. The PCI values obtained varied between 6 and 78, with 60% of segments categorized as poor to failed, and only 10% in satisfactory condition. These findings indicate that most road sections are in unserviceable conditions and require structural handling. Based on the PCI value classification, reconstruction actions are recommended for segments with PCI < 55, overlay and structural maintenance for PCI 55–70, and preventive maintenance for PCI > 70. This study confirms the importance of implementing PCI as a technical decision-making tool in sustainable road maintenance planning.